Cohort study to characterise surgical site infections after open surgery in the UK’s National Health Service - Julian F Guest; Graham W Fuller; Ben Griffiths (BMJ Open, 2023)
Objective To characterise surgical site infections (SSIs) after open surgery in the UK’s National Health Service.Design Retrospective cohort analysis of electronic records of patients from Clinical Practice Research Datalink, linked with Hospital Episode Statistics’ secondary care datasets.Setting Clinical practice in the community and secondary care.Participants Cohort of 50 000 adult patients who underwent open surgery between 2017 and 2022.Outcome measures Incidence of SSI, clinical outcomes, patterns of care and costs of wound management.Results 11% (5281/50 000) of patients developed an SSI a mean of 18.4±14.7 days after their surgical procedure, of which 15% (806/5281) were inpatients and 85% (4475/5281) were in the community after hospital discharge. The incidence of SSI varied according to anatomical site of surgery. The incidence also varied according to a patient’s risk and whether they underwent an emergency procedure. SSI onset reduced the 6 months healing rate by a mean of 3 percentage points and increased time to wound healing by a mean of 15 days per wound. SSIs were predominantly managed in the community by practice and district nurses and 16% (850/5281) of all patients were readmitted into hospital. The total health service cost of surgical wound management following SSI onset was a mean of £3537 per wound ranging from £2542 for a low-risk patient who underwent an elective procedure to £4855 for a high-risk patient who underwent an emergency procedure.Conclusions This study provides important insights into several aspects of SSI management in clinical practice in the UK that have been difficult to ascertain from surveillance data. Surgeons are unlikely to be fully aware of the true incidence of SSI and how they are managed once patients are discharged from hospital. Current SSI surveillance services appear to be under-reporting the actual incidence.